"I'm just a child having a child" : an exploration of the experiences of pregnant teenagers and young mothers in a low socio-economic urban area. - Sowden, Linda (My University, 2013)
This research project looks at the experiences of a group of pregnant teenagers in a low socio-economic area. Teenage sexuality and pregnancy has been the subject of substantial research in South Africa and the rest of the world as it is a global issue. The challenge that pregnant teenagers face are to manage schooling, pregnancy and mothering rather than dropping out of school. This study was conducted using a qualitative research method through semi-structured interviews. The participants consisted of fourteen teenagers ranging from fifteen to eighteen years of age. The teenagers were either pregnant or had delivered their babies. They attended the local high school with the exception of one participant who had dropped out of school. I interviewed one Life Orientation educator from the local high school and one ante natal nursing sister from the local municipal clinic. Teenage pregnancy produced gender inequalities as the female adolescent is unable to attend school whilst recuperating from the birth of the child; the male continues attending school regardless of fathering the child. Culturally it was inappropriate to receive sex education at home so information was gained within the formal setting of Life Orientation classes, peers or social media. Due to varying degrees of familial support, the teenagers were able to return to school after the birth of their babies. The level of family support ranged from taking over full responsibility of the child so the adolescent continued with her former life to the teenager having to care for the child when returning from school and only being able to complete homework tasks once the baby was asleep. Agency was most apparent in the decision of abortion. The teenagers would not be forced into the procedure if it was not the option of their choice despite pressure from boyfriends and family. Teenagers also showed agency in ending relationships with their partners if the partner was dating other girls concurrently. However, they did not use agency in the negotiation of condom use despite stating that they were in equal relationships with their boyfriends. This indicates how structures may constrain agency, specifically structures that are located in gendered inequalities. The teenagers were knowledgeable about the facts of condom use as protection against pregnancy and disease but these facts were not put into practice. Discourses suggest female teenagers’ fear of being rejected by their partner through the insistence of condom use and male domination over the female.
Keywords: Teenage mothers--South Africa.; Teenage pregnancy--Psychological aspects.; Low-income mothers--South Africa--Social conditions.